Electrically Switchable Color Tags Based on Active Liquid‐Crystal Plasmonic Metasurface Platform. Issue 7 (20th January 2020) - Sharma, Mukesh; Hendler, Netta; Ellenbogen, Tal
Abstract: Recent demonstrations of metasurfaces show their great potential to realize flat and multifunctional optical elements, viable for many new device applications. Yet, a major frontier in this field is to develop active, tunable, and reconfigurable metasurface platforms. These are highly desirable in modern technologies that require dynamic modulation of light. To achieve this goal, in this work an active liquid‐crystal (LC) plasmonic metasurface integrated system is developed and studied. It is specifically used to demonstrate electrically switchable plasmonic‐metasurface‐based color tags. The active tags utilize the ability to rotate the polarization of incident light, by application of an external electric field on twisted nematic liquid crystal configuration. Combined with the wavelength and polarization‐selective response of the metasurface, it allows to obtain electrically controlled transmission colors potentially spanning the entire visible spectrum. It is experimentally demonstrated that the dynamic wavelength shift in the devices is greater than 100 nm at a low driving voltage varying from 0 to 5 V. These experimental results indicate the potential of active LC‐plasmonic metasurface platforms to realize the next‐generation dynamic optical devices. Abstract : Electrically switchable color tags based on liquid‐crystal (LC) plasmonic metasurface platform are demonstrated. The active tags utilize the ability to rotate the polarization of incident light, by application of electric field on twisted nematic LC configuration. The dynamic wavelength shift can potentially cover the entire visible spectrum at a low driving voltage varying from 0 to 5 V.